Assessment of the baseline pattern of fetal heart rate using software algorithms - Leila Ahmadi; Mehdi Rashedin; Roghaieh Kharaghani (Zanjan University of Medical Sciences and Health Services, 2019)
Background: Currently, fetal heart monitoring is the most widely used primary method for assessing fetal health. Objectives: The current study intended to investigate the baseline patterns of fetal heart rate using software technology. Methods: This is a software design study. Medical records of maternal deliveries of Mousavi Hospital in Zanjan were examined using the convenience sampling method and required information were collected and the fetal heart monitoring strips were scanned. The tests were interpreted by three faculty members with a clinical background and related experience in teaching from the Zanjan and Tehran Universite of Medical Sciences. The strips were also interpreted using software designed by computer engineers without knowing the results of the research medical team. The accuracy of the diagnoses made by the software was compared against the diagnosis made by the skilled faculty members. Results: The mean (standard deviation) of the baseline feat heart rate calculated by the software was 142.06 (10.61) and the mean of the rate calculated by the skilled faculty members was 142.08 (10.77). There was a 95.9% correlation between the baseline calculated by the software and by experts (p<0.001). Besides, 92.1% of the baseline variance calculated by the software was determined by the baseline calculated by the experts (p<0.001). Softwarechr('39')s reports on fetal tachycardia had 100% sensitivity and 98.7% specificity and, for fetal bradycardia, reports had 100% sensitivity and 99.7% specificity, compared to the expertchr('39')s report. Conclusion: According to the results, the software can be useful for health staff to accurately diagnose the baseline pattern of fetal heart rate and its related disorders.